ChemInform Abstract: Bioactive Constituents from Radermachera boniana. Issue 44 (13th October 2016) - Wang, Ming‐Zhong; Xie, Wen‐Jian; Guan, Yi‐Fu; Song, Xun; Hung, Nguyen Van; Cuong, Nguyen Manh; Santarsiero, Bernard D.; Fong, Harry H.S.; Soejarto, D. Doel; Zhang, Hong‐Jie
Abstract: 17 Naphthalene‐based quinones are isolated from the roots of Radermachera boniana Dop.